COAGULASE-NEGATIVE Staphylococci AND THEIR PATHOGENIC ROLE: A FOCUS ON NOSOCOMIAL INFECTIONS (Applied Biological Research, 2023)
Staphylococci, involved in many human diseases, are present on human  and animal body surfaces as well as in air, food and water. The general  classification of staphylococci divides them in two major groups; coagulase  positive and negative staphylococci. Coagulase-negative staphylococci  (CoNS) are present as a part of normal skin andmucous membrane flora  in humans. CoNS have long been considered as non-pathogenic organism  but now they are considered pathogenic involved in infections related to  prosthetic materials particularly in surgicalwounds. Virulence factors in  CoNS are not very clearly established. Staphylococcus epidermidis is  evolving as a resistant and powerful microbe related to nosocomial  infections. Characteristics like biofilm formation, drug resistance and  evolution of genetic variables contribute to its pathogenicity. This review  elaborates the evidence of involvement of CoNS in various clinically  important infections from recent and past literature.
Keywords: Biofilm; coagulase-negative staphylococci; nosocomial infections; S. epidermidis